A surgical training model manufacturer using fused deposition (FDM) modeling - Wan Yusoff, Wan Ahmad Yusmawiza (s.n, 2013)
The purpose of this research is to study and apply the use of rapid prototyping technology as a great value tool in supporting medical activity. Its is possible to produce three-dimensional model from two-dimensional images from Computerized Tomography (CT) can where the machine provides images data are used to capture. Rapid Prototyping (RP) is technology from mechanical engineering that is used to fabricate physical prototypes called bio-medical model that can be used for surgical planning. The models produced by using RP bring the significant in educational and pre-medical surgical environment